Synthesis Polysulfone-Acetylethanol Ultrafiltration Membranes. Application to Oily Wastewater Treatment - Masuelli, Martin Alberto (2013)
Chemical functionalization of polymers after the synthesis of membranes has great importance for various applications separative processes of industrial or environmental interest. Polysulfone (PSf) is one of the most applied polymers for separative processes used especially in membrane technology, due to its excellent chemical, mechanical and thermal properties. The functionalization of PSf makes it very attractive to give special characteristics due to their high hydrophobicity and membrane fouling fast. In this work PSf perform functionalization by the method of Friedel-Crafts with choroethyl chloroacetate and subsequent hydrolysis of chloroetyl group (-OH). After synthesizing the membrane is characterized by FT-IR ATR spectroscopy, 1HNMR, contact angle measurements, retention of polydisperse solutes and hydraulic permeability. Finally, the membranes tests fouling are performed with an oily wastewater emulsion. The fouling tests showed that the functionalized PSf membrane demonstrated significant anti-fouling property, suggesting the remarkable benefit for long-term operation in practical applications. Specifically, all the functionalized membranes reached almost 60% water flux recovery and were able to maintain the constant initial fluxes in filtration test, whereas the raw membrane only recovered 70.27% and suffered continuous decline. This promotion might be related to the increase of membrane surface hydrophilicity.